2021
DOI: 10.1038/s41598-020-80454-3
|View full text |Cite
|
Sign up to set email alerts
|

De novo assembled salivary gland transcriptome and expression pattern analyses for Rhipicephalus evertsi evertsi Neuman, 1897 male and female ticks

Abstract: Ticks secrete proteins in their saliva that change over the course of feeding to modulate the host inflammation, immune responses, haemostasis or may cause paralysis. RNA next generation sequencing technologies can reveal the complex dynamics of tick salivary glands as generated from various tick life stages and/or males and females. The current study represents 15,115 Illumina sequenced contigs of the salivary gland transcriptome from male and female Rhipicephalus evertsi evertsi ticks of early, mid and late … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 115 publications
0
3
0
Order By: Relevance
“…Adult females require a blood meal as a rich source of heme for producing viable eggs, and many adult males require a blood meal to produce viable sperm [39,51]. In at least two tick species, males and females have different salivary protein profiles [52][53][54], although it has not been investigated if this impacts viral transmission.…”
Section: Ticksmentioning
confidence: 99%
“…Adult females require a blood meal as a rich source of heme for producing viable eggs, and many adult males require a blood meal to produce viable sperm [39,51]. In at least two tick species, males and females have different salivary protein profiles [52][53][54], although it has not been investigated if this impacts viral transmission.…”
Section: Ticksmentioning
confidence: 99%
“…The paired end reads were merged to produce a merged dataset (Merged), while the single reads were used as unpaired (Single) and to produce a single-merged dataset (SM). Duplicates were also removed from these datasets to produce three duplicate removed datasets (Mddup, Sddup, and SMddup;Pienaar et al, 2021). These datasets were used to assemble the transcriptome using Trinity v2.4.0 and CLC Genomics Workbench v 20.0.…”
Section: Transcriptome Assemblymentioning
confidence: 99%
“…These salivary modulations could be pathogen directed and favorable to the vector host in order to co-exist and benefit each other from this long-term relationship. There are several studies including transcriptomics/proteomics and sialomics, with evidence that tick-transmitted pathogens manipulate the salivary/saliva components to facilitate their transmission, evade host defense reactions and survive in the vertebrate host [35][36][37][38][39][41][42][43][44][45][46][47] . Our findings revealed that tick exosomes are salivary/saliva components and that they do facilitate pathogen transmission to the vertebrate host, suggesting that they are novel means of the dissemination from vector to the vertebrate host [3,24] .…”
Section: Introductionmentioning
confidence: 99%